Pembangunan Sistem Informasi Manajemen Agenda Kegiatan Berbasis Web di BPS Provinsi Nusa Tenggara Barat - Dupayana, I Putu Agus Wahyu; Anang, Yunarso (Seminar Nasional Official Statistics, 2024)
The simplification of the organizational structure by BPS-Statistics Indonesia aims to form a simpler institution to support performance more effectively and efficiently. Challenges arise in the implementation of this simplification at Statistics of NTB Province, particularly with the division into several work teams leading to activity overlap. As a solution, it can be considered to develop an information system. The data collection method used involves interviews and observation, while system development follows the prototype model in the Software Development Life Cycle (SDLC). System evaluation was carried out using the Post-Study System Usability Questionnaire (PSSUQ). System development has gone through three iterations according to user needs and test results show the system is ready for use. After system integration on the server and system handover, an evaluation of system usability is carried out with PSSUQ. The evaluation results show that overall, the system provides good use for Statistics of NTB Province.